0.20(6)+0.05x=0.10(24+x)

Simple and best practice solution for 0.20(6)+0.05x=0.10(24+x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0.20(6)+0.05x=0.10(24+x) equation:


Simplifying
0.20(6) + 0.05x = 0.10(24 + x)

Multiply 0.20 * 6
1.2 + 0.05x = 0.10(24 + x)
1.2 + 0.05x = (24 * 0.10 + x * 0.10)
1.2 + 0.05x = (2.4 + 0.10x)

Solving
1.2 + 0.05x = 2.4 + 0.10x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-0.10x' to each side of the equation.
1.2 + 0.05x + -0.10x = 2.4 + 0.10x + -0.10x

Combine like terms: 0.05x + -0.10x = -0.05x
1.2 + -0.05x = 2.4 + 0.10x + -0.10x

Combine like terms: 0.10x + -0.10x = 0.00
1.2 + -0.05x = 2.4 + 0.00
1.2 + -0.05x = 2.4

Add '-1.2' to each side of the equation.
1.2 + -1.2 + -0.05x = 2.4 + -1.2

Combine like terms: 1.2 + -1.2 = 0.0
0.0 + -0.05x = 2.4 + -1.2
-0.05x = 2.4 + -1.2

Combine like terms: 2.4 + -1.2 = 1.2
-0.05x = 1.2

Divide each side by '-0.05'.
x = -24

Simplifying
x = -24

See similar equations:

| 3x(x-2)(2x+1)=0 | | -99-8=7x+21 | | 7-10x=131-38x | | 103-3x=15x+23 | | .44y^2+1=0 | | 3(y+2)-2=2(4-y) | | 3(y+2)-2=2(41y) | | 5s-19s=28 | | 4t+3=t-18 | | 8+2x*3=x*4+12 | | a^2x+3x=2a^2 | | x^2-5.75+7.75=6 | | x^2-5.75+7.75=1 | | x^2-5.75+7.75=4 | | x^2-5.75+7.75=2 | | 2x^2-4x+8.8=2 | | 2x^2-4x+18.2=2 | | 5a^2-6a=1 | | (10b-6)-3(3b+2)=-3 | | x^2-8x+15.75=0 | | y=0(0)-7 | | (4y+9)(4y+9)=64y^3+432y^2+972y+729 | | 5c+6=2-y | | 5x+6x+3+8=3x+5+7x | | 16+-8-9= | | z^2-8z-20= | | 3(Q-6)=2(2Q+7)+10 | | 25+-15-12= | | 15x^2+5x-20= | | y=18(0)+0 | | 9y^2+21y+6= | | 2x+3x=30-z |

Equations solver categories